Den utæmmelige kraft: Magisk aktivisme som reaktion på det reaktionæres genkomst - Opstrup, Kasper (K&K - Kultur og Klasse, 2018)
This article discusses magical thinking and the witch in relation to activism and the return of reactionary politics. It traces a technique of magical activism that utilises irrational images and the occult as fictionalisation strategies to create change. This technique is not only used by power to control and govern or to help the extreme right in normalising their ideas. It is also the terrain for a battle of who we are and who we can be. It is more an apparatus than an ideology and can thus, is and has been used across the political spectrum. Throughout the article, I pay special attention to memes and the contemporary turn towards a politicised witchcraft with three examples, all with an explicit anti-Trump agenda: The Magic Resistance, W.I.T.C.H.pdx, and the Yerba Mala Collective. By reclaiming language and stigmatised, historical figures as potential political tools, the ideology of witchcraft empowers the individual to not only manifest her will, but to believe that our collective will is able to change what is, and bring hope to a time characterised by isolation and impotence. But while they can carry an anti-authoritarian promise of freedom, these pop-cultural myths can also be the carriers of a normalisation of essentially fascist ideas. The occult was part of the libidinal energies released by the countercultures up through the 1960s and 70s. Due to that the established left wing was not able to contain these energies, they became part of the re-individualisation project of the right from the 1980s onwards. Today, its shadows can be traced not only on the anti-authoritarian left but also in various neo-con and alt-right circles. The methods and techniques of magic for self-transformation release energy, but also fits perfectly into our contemporary structures of dominance while it still bring hope to a hopeless situation.